Role of preoperative cervical alignment on postoperative dysphagia after occipitocervical fusion - Miyagi, Midori (Surg Neurol Int, 2021)
BACKGROUND: Dysphagia is one of the most serious complications of occipitocervical fusion (OCF). The previous studies have shown that postoperative cervical alignment, documented with occipito (O)-C2 angles, C2-C6 angles, and pharyngeal inlet angles (PIA), impacted the incidence of postoperative dysphagia in patients undergoing OCF. Here, we investigated the relationship of preoperative versus postoperative cervical alignment on the incidence of postoperative dysphagia after OCF. METHODS: We retrospectively reviewed the clinical data/medical charts for 22 patients following OCF (2006– 2019). The O-C2 angles, C2-C6 angles, PIA, and narrowest pharyngeal airway spaces (nPAS) were assessed using plain lateral radiographs of the cervical spine before and after the surgery. The severity of dysphagia was assessed with the functional oral intake scale (FOIS) levels as documented in medical charts; based on this, patients were classified into the nondysphagia (FOIS: 7) versus dysphagia (FOIS: 1–6) groups. RESULTS: Seven patients (35%) experienced dysphagia after OCF surgery. Preoperative PIA and nPAS were smaller in the dysphagia group. Spearman rank correlation showed a positive correlation between preoperative PIA and FOIS and between preoperative nPAS and FOIS. CONCLUSION: This study suggests that preoperative cervical alignment may best predict the incidence of postoperative dysphagia after OCF.